Pengaruh Bystander Effect, Ketaatan Aturan Akuntansi dan Efektivitas Pengendalian Internal Terhadap Kecenderungan Fraud Akuntansi Di Lembaga Perkreditan Desa (LPD) Se-Kecamatan Susut Kabupaten Bangli - Ni Luh Ita Pratiwi; Ni Komang Sumadi; Ni Putu Trisna Windika Pratiwi (UNHI Press, 2023)
This research is structured with the aim of analyzing what factors can influence the level of accounting fraud tendency in a company. In this study, several factors will be analyzed, namely the bystander effect, compliance with accounting rules and the effectiveness of internal controls. bystander effect, compliance with accounting rules and effectiveness of internal control. This study uses LPD employees as the research population where the number of samples is 75 people. This study uses multiple linear regression analysis techniques with the result that an increase in the bystander effect in the institution will actually lead to an increase in fraud. Compliance with accounting rules and the effectiveness of internal controls that are continuously improved are proven to be able to reduce the possibility of fraud in the organization. The advice given by the researcher is that the LPD in the Shrinking District is expected to always protect employees who dare to report fraud, besides that the LPD in the Shrinking District should give strict sanctions to employees who do not comply with accounting rules and the LPD in the Shrinking District is expected to implement internal control properly.